Developing a web-based instruction platform using RME approach to support students’ conceptual understanding - Ika Surtiani; Hartono Hartono (Universitas Ahmad Dahlan, 2026)
Trigonometry is often considered one of the most difficult topics for high school students, with many struggling due to a weak conceptual understanding. This study aims to develop a web-based instruction (WBI) platform called Sine and Shine using the Alessi and Trollip development model. It is a structured web-based teaching program and self-regulated learning resource designed to strengthen the students’ understanding of trigonometry concept. We designed the WBI to have various characteristics, such as interactive features, contextual problems, guided feedback, and integrating the principles of Realistic Mathematics Education (RME) in it. We involved 21 students as the participants to evaluate the platform using a mixed-method approach. In terms of validity, the experts unanimously judged that the Sine and Shine platform is strongly valid. In terms of practicality, the teacher and students feedback confirmed that the platform was very practical. In terms of effectiveness, we conducted a statistical analysis and found out that the mean score of post-test was 83.44, significantly higher than the school’s minimum mastery criteria (t = 6.1602, p = 2.87e-06), and the paired sample t-test between pre- and post-tests yielded p = 7.20e-16. The normalized gain score was 0.72, indicating a high level of improvement in conceptual understanding. These results demonstrate that Sine and Shine is a valid, practical, and effective digital learning tool that significantly enhances the students’ understanding of trigonometry and promotes self-regulated learning.